The Linguistic Problem and The Thinking Skill in The Arabic Debate at the ICIS Club at UIN Kiai Haji Achmad Siqqiq in Jember: المشكلة اللغوية ومهارة التفكير في نشاط المناظرة باللغة العربية بنادي ICIS في جامعة كيائي هاجي أحمد صديق الإسلامية الحكومية بجمبر - Wihdatul Hasanah; Faris Maturedy; Taha Ramadan Zaghloul (Journal of Arabic Language Teaching, 2022)
The debate exercise was conducted for the new members of the ICIS Club at Kiai Hagi Ahmad Siddiq State Islamic University. They had problems with their workout. Therefore, the research aims to describe these problems, but this is limited to the linguistic problem and the problem of thinking efficiency. In this research, the qualitative research method was used. The data was collected through personal interview and observation. The data was therefore analyzed in a descriptive manner. The results of the research are that the new debaters face two problems throughout an Arabic debate exercise. They are the linguistic problem and the problem of thinking efficiency. The linguistic problem is that they are not used to using contemporary methods and vocabulary in the terminology of debate. The problem with thinking efficiency is that they do not use the three-Ds method to make the case for non-habituation. They are affirmation, reasoning and demonstration Keywords: Speaaking Skill, Debate, HOTS